Access to PrEP and other sexual health services for cisgender women in the United States: a review of state policy and Medicaid expansion - Chory, Ashley; Bond, Keosha (Frontiers in Public Health, 2024)
Pre-exposure prophylaxis (PrEP) has the potential to prevent new HIV infections, but it is unclear how state policies governing sexual and reproductive health services (SRH) impact access for cisgender women. The objective of this review is to identify barriers to PrEP access for cisgender women in the United States. Using the CDC Atlas Program, twenty states with the highest HIV incidence among cisgender women were included in this analysis. Through a search conducted in May-July 2022 of CDC, PrEPWatch.org, and other State Department and Insurance websites, Medicaid expansion status, pharmacist PrEP prescribing laws, financial support programs, and Traditional Medicaid coverage of PrEP, HIV testing, and emergency fcontraception were reviewed. Of the included states, nearly half did not expand Medicaid at the state level. Emergency contraception and HIV testing was covered under Traditional Medicaid for almost all included states, but insurance stipulations and eligibility requirements remain.Although PrEP is covered under all Traditional Medicaid plans, six states require preauthorization. Three states have HIV testing mandates, four allow pharmacists to prescribe PrEP and six have financial support programs to cover the cost of PrEP. Medicaid expansion, preauthorization requirements for PrEP prescriptions and emergency contraception, and limitations on pharmacist prescribing abilities were identified as barriers to SRH access for cisgender women. Medicaid expansion should be prioritized as an approach to expanding access to HIV prevention services at the state level.